Air-stable and efficient electron doping of monolayer MoS2 by salt–crown ether treatment. Issue 19 (30th April 2021) - Ogura, Hiroto; Kaneda, Masahiko; Nakanishi, Yusuke; Nonoguchi, Yoshiyuki; Pu, Jiang; Ohfuchi, Mari; Irisawa, Toshifumi; Lim, Hong En; Endo, Takahiko; Yanagi, Kazuhiro; Takenobu, Taishi; Miyata, Yasumitsu
Abstract : The present doping technique demonstrates the highly efficient electron doping of monolayer MoS2 with high stability under ambient conditions using KOH/benzo-18-crown-6 as the dopant. Abstract : To maximize the potential of transition-metal dichalcogenides (TMDCs) in device applications, the development of a sophisticated technique for stable and highly efficient carrier doping is critical. Here, we report the efficient n-type doping of monolayer MoS2 using KOH/benzo-18-crown-6, resulting in a doped TMDC that is air-stable. MoS2 field-effect transistors show an increase in on-current of three orders of magnitude and degenerate the n-type behaviour with high air-stability for ∼1 month as the dopant concentration increases. Transport measurements indicate a high electron density of 3.4 × 10 13 cm −2 and metallic-type temperature dependence for highly doped MoS2 . First-principles calculations support electron doping via surface charge transfer from the K/benzo-18-crown-6 complex to monolayer MoS2 . Patterned doping is demonstrated to improve the contact resistance in MoS2 -based devices.